PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. PETROKOPINDO CIPTA SELARAS - Listiana, Tri; Suaibatul Aslamiyah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
This study aims to examine the influence between the variables of work motivation, work discipline, and work environment on employee productivity at PT Petrokopindo Cipta Selaras partially. This research uses quantitative research methods. The population in this study were all employees of PT Petrokopindo Cipta Selaras, totalling 184 people. The sampling of this study is called simple random sampling using the Slovin formula with a sample of 126 samples. The approach used in this research is Structural Equation Model (SEM) with SmartPLS analysis tool. The results of this study are that there is a positive and significant effect partially because the t statistical value> 1.96 means significant and if the p value <0.05 in this study the results obtained are 0.00, it means that it has an effect (h1 is accepted). the conclusion is that work motivation, work discipline, and work environment have a positive and significant effect on the work productivity of employees of PT Petrokopindo Cipta Selaras.